1995
DOI: 10.1115/1.2822321
|View full text |Cite
|
Sign up to set email alerts
|

Local Heat Transfer in Axially Feeding Radial Flow Between Parallel Disks

Abstract: Experiments and computations were performed to determine the local heat transfer in radial flows between parallel concentric disks. The flow is supplied axially by a feeding orifice placed in one of the disks and becomes radial after being deflected by the frontal disk. The frontal disk is kept isothermal and the other solid surfaces washed by the flow are kept adiabatic. Local heat transfer coefficients were determined using the naphthalene sublimation technique and the analogy between heat and mass transfer.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…They found that the heat transfer coefficient converges to 4.93 for slug flows and 3.77 for fully developed creeping flows. Their results were in good agreement with experimental data from Prata et al (1995), who considered radial diffusers with varying Υ at Reynolds numbers between 600 and 4595.…”
Section: Introductionsupporting
confidence: 87%
“…They found that the heat transfer coefficient converges to 4.93 for slug flows and 3.77 for fully developed creeping flows. Their results were in good agreement with experimental data from Prata et al (1995), who considered radial diffusers with varying Υ at Reynolds numbers between 600 and 4595.…”
Section: Introductionsupporting
confidence: 87%
“…(1). The local Sherwood number is then determined by: (3) with L a reference length, the air gap thickness in the case of a rotor stator system [PRA95] or jet diameter in [CHE98], and the diffusion coefficient of the naphthalene vapor in the air, which is usually obtained with an equation of the following form: (4) where T is the air temperature inside the gap or near the disk. Depending on the author, a ranges from to and b from 1.75 to 1.983.…”
Section: Convective Heat Transfermentioning
confidence: 99%
“…with L a reference length, the air gap thickness in the case of a rotor stator system [PRA95] or jet diameter in [CHE98], and the diffusion coefficient of the naphthalene vapor in the air, which is usually obtained with an equation of the following form:…”
Section: Convective Heat Transfermentioning
confidence: 99%
“…9 that of the six points used in Eq. (18), two are at the interface and, therefore, their values are known from the prescribed boundary condition.…”
Section: Discretization For Interfacial Volumesmentioning
confidence: 99%
“…On the other hand, the interaction between the flow field and the valve dynamics is quite complex and very few studies have modeled such a solid-fluid interaction [16]. For fluid flow in radial diffusers in the context of compressor valves the reader is referred to Ferreira et al [4], Prata and Ferreira [17], Prata et al [18], Deschamps et al [2], and Ferreira and Driessen [3].…”
Section: Introductionmentioning
confidence: 99%